2012
DOI: 10.1093/brain/aws239
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and post-mortem memory circuit integrity in frontotemporal dementia and Alzheimer’s disease

Abstract: Behavioural variant frontotemporal dementia can present with episodic memory deficits as severe as those in Alzheimer's disease. Little is known of the integrity of grey matter areas and white matter tracts of the Papez memory circuit in these diseases. The integrity of the Papez circuit (hippocampus, fornix, mammillary bodies, anterior thalamus, cingulate cortex) was investigated in vivo and at post-mortem in behavioural variant frontotemporal dementia and Alzheimer's disease cohorts using voxel-based morphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
142
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 160 publications
(157 citation statements)
references
References 52 publications
12
142
2
1
Order By: Relevance
“…Hippocampal atrophy is well documented in bvFTD [32] and has been shown to correlate robustly with episodic memory dysfunction in this group [6]. Accordingly, compromised PM performance in bvFTD may reflect disruption of the retrospective memory search processes required to retrieve the intended action, a process which is mediated by the hippocampus [56].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hippocampal atrophy is well documented in bvFTD [32] and has been shown to correlate robustly with episodic memory dysfunction in this group [6]. Accordingly, compromised PM performance in bvFTD may reflect disruption of the retrospective memory search processes required to retrieve the intended action, a process which is mediated by the hippocampus [56].…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, given mounting evidence pointing to the involvement of the hippocampus in the genesis of EM dysfunction in bvFTD [6,32], we predicted that the hippocampus would represent a common neural correlate across the two disease syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…In more details, the preservation of episodic memory in bvFTD has been recently challenged by an increasing number of independent studies showing that bvFTD patients can present with similar levels of amnesia as Alzheimer's disease, [4,5] with both manifesting a combination of frontally mediated and storagebased memory impairment. Although previous studies have suggested that prefrontal cortex degeneration might be the greatest determinant of amnesia in bvFTD, [21,22] more recent evidence suggest that bvFTD patients also show severe atrophy of the medial temporal lobes, including the hippocampus as well as the entire Papez circuit.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have suggested that prefrontal cortex degeneration might be the greatest determinant of amnesia in bvFTD, [21,22] more recent evidence suggest that bvFTD patients also show severe atrophy of the medial temporal lobes, including the hippocampus as well as the entire Papez circuit. [4,6] One of the only studies that cross-correlated episodic memory performance with grey matter intensity in bvFTD and Alzheimer's disease showed that posterior parietal and cingulate regions were implicated exclusively in Alzheimer's disease while temporal poles and medial frontal regions were involved specifically in bvFTD. [8] Although the profile of cortical involvement in episodic amnesia is different in bvFTD and Alzheimer's disease, current available episodic memory assessments (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation